IBADAH QURBAN SEBAGAI WUJUD IMAN DAN TAQWA DALAM MENYUKSESKAN PEMBANGUNAN - Muhammad Zakariah (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
Qurban (sacrifice praying) has two aspects, namely the divine aspect and the aspect of ijtimaiyah. Vertical or divine aspect in order to get closer to God, taqarrub ilallah. And the horizontal or ijtimaiyah aspect is the effort to bring a sense of closeness, connect silahturahmi with fellow human. The essence of the essence of qurban worship is sincerity. Sincerity sacrifices some of our loved ones and enjoys them for interests beyond our interests. Sincere nature will flourish as the fruit of Iman (faith) and taqwa (Godly). If we are given the trust to be leaders, we sincerely sacrifice to guide, nurture and serve our society with full wisdom and justice. Awareness to do qurban in the celebration of Eid al-Adha becomes the momentum for those who are able to be more concerned to the faqir, poor or dhuafa to make development of social awareness movement more real in social environment.